Effects of increased reading rate on covert processes - McGuigan, F. J.; Pinkney, Kathy Blake (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Three experiments, one with adults and two with children, were conducted to determine whether increasing reading rate affects covert oral behavior, and other covert processes. Previous findings were confirmed that during silent reading there is heightened covert oral behavior, increased respiration rate and decreased EEG amplitude, and there was essentially no change in leg EMG or pulse rate. Increased reading rate produced a decrease in end of line eye movements (indicating that the subjects learned to read more than one line at a time) and apparently increased amplitude of tongue EMG; the increased covert oral behavior as a result of increased reading rate was more apparent in adults than in children. Perhaps heightened covert oral behavior facilitates the reading process.